2023
DOI: 10.47391/jpma.6432
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periodontal disease in pregnancy for the prevention of adverse pregnancy outcomes: a systematic review of systematic reviews

Abstract: Objective: To assess the systematic reviews and meta-analyses investigating whether or not periodontal treatment in pregnancy was effective in reducing the adverse pregnancy outcomes of preterm birth, low birth weight, preterm low birth weight, stillbirth, foetal growth restriction, and pre-eclampsia. Method: The umbrella review was conducted on May 30, 2021, and comprised search of electronic databases MEDLINE, EMBASE, Cochrane Database of Systematic Reviews via Ovid and CINAHL via EBSCO for all systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Regarding the methodological quality, four of five umbrella reviews used AMSTAR-1 (the first version of this tool, published in 2007), whereas only two umbrella reviews [35,37] used AMSTAR-2 as we did. Furthermore, Condylis et al [15] did not assess the methodological quality of the evidence of the included studies at all, which can be considered a serious methodological flaw.…”
Section: Agreement and Disagreement With Previous Umbrella Reviewsmentioning
confidence: 68%
See 1 more Smart Citation
“…Regarding the methodological quality, four of five umbrella reviews used AMSTAR-1 (the first version of this tool, published in 2007), whereas only two umbrella reviews [35,37] used AMSTAR-2 as we did. Furthermore, Condylis et al [15] did not assess the methodological quality of the evidence of the included studies at all, which can be considered a serious methodological flaw.…”
Section: Agreement and Disagreement With Previous Umbrella Reviewsmentioning
confidence: 68%
“…To the best of the authors' knowledge, eight umbrella reviews addressed and summarized the available evidence in this association between periodontitis and APOS, and the effect of periodontal disease on pregnancy complications [15][16][17][18][19][35][36][37]. In all eight published umbrella reviews, the authors only analyzed and interpreted the methodological quality and described the main findings of the included systematic reviews on maternal periodontitis and APOs.…”
Section: Agreement and Disagreement With Previous Umbrella Reviewsmentioning
confidence: 99%
“…These results were confirmed in a longitudinal cohort study conducted in Chile, which included 870 people, where the treatment of PD significantly reduced the rate of PB and LBW in women with pregnancy-associated gingivitis [ 74 ]. However, in a recent analysis, Khan et al [ 22 ] evaluated 17 SRs and concluded that the evidence on this topic is inconclusive, because there are insufficient clinical trials, causing them to present high possibilities of bias in the research, because it is not possible to evaluate some specific aspects such as the diagnosis, extension, and severity of the disease [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This possibility gave rise to a number of interventional studies, conducted in recent years, to investigate the association between PD and adverse pregnancy outcomes [ 21 ], leading to the publication of an umbrella systematic review on this association in 2023 [ 22 ], but systematic reviews continue to be published, so an update is necessary.…”
Section: Introductionmentioning
confidence: 99%